Evaluation of Cuspidaria pulchra and its Isolated Compounds Against Schistosoma mansoni Adult Worms - Alvarenga, Tavane A.; Bêdo, Tais R.F.O.; Braguine, Caio G.; Gonçalves, Ubirajara O.; Magalhães, Lizandra G.; Rodrigues, Vanderlei; Gimenez, Valéria M.M.; Groppo, Milton; Silva, Márcio Luis A.; Cunha, Wilson R.; Januário, Ana H.; Pauletti, Patrícia M. (International Journal of Biotechnology for Wellness Industries, 2012)
The present study has investigated the chemical composition of the bioactive EtOAc fraction of Cuspidaria pulchra aerial parts, as well as its schistosomicidal activities against Schistosoma mansoni adult worms in vitro. To this end, the crude ethanol extract obtained from the aerial parts of Cuspidaria pulchra (Bignoniaceae) was partitioned with n-hexane, EtOAc, and n-BuOH. The EtOAc fraction was purified by preparative HPLC, which afforded 3,4-dihydroxybenzaldehyde (1), p-coumaric acid (2), p-hydroxybenzoic acid (3), ursolic acid (4), and oleanolic acid (5). The bioassay results indicated that the crude ethanol extract and the EtOAc fraction at 100 µg/mL killed the adult schistosomes in vitro. Compounds 1 and 3 at 100 µm were only able to separate coupled S. mansoni adult worms.